Corrosion Resistance of Synergistic Welding Process of Aluminium Alloy 6061 T6 in Sea Water - Hassan, Kharia Salman (Al-Khwarizmi Engineering Journal, 2017)
Abstract This work involves studying corrosion resistance of AA 6061T6 butt welded joints using Two different welding processes, tungsten inert gas (TIG) and a solid state welding process known as friction stir welding, TIG welding process carried out by using Rolled sheet of thickness6mm to obtain a weld joint with dimension of (100, 50, 5) mm using ER4043 DE (Al Si5) as filler metal and argon as shielding gas, while Friction stir welding process carried out using CNC milling machine with a tool of rotational speed 1000 rpm and welding speed of 50mm/min to obtain the same butt joint dimensions. Also one of weld joint in the same dimensions subjected to synergistic weld process TIG and FSW weld process at the same previous weld conditions. All welded joints were tested by X-ray radiography and Faulty pieces were excluded. The joints without defects used to prepare many specimens for Corrosion test by the dimensions of (15*15*3) mm according to ASTM G71-31. Specimens subjected to micro hardness and microstructure test. Corrosion test was achieved by potential at scan rate( +1000 ,-1000mv/sec) to estimate corrosion parameters by extrapolator Tafle method after polarized ±100 mv around open circuit potential,in seawater (3.5%NaCl) at a temperature of 25°C. From result which obtained by Tafel equation. It was found that corrosion rate for TIG weld joint was higher than the others but synergistic weld process contributed in improving TIG corrosion resistance by a percentage of 14.3%. and FSW give the lest corrosion rate comparing with base metal.